Anthropometric measures and blood pressure of Greenlandic preschool children. Issue 1 (1st January 2021) - Kok Grouleff, Magnus; Wielsøe, Maria; Berthelsen, Dina; Mulvad, Gert; Isidor, Silvia; Long, Manhai; Bonefeld-Jørgensen, Eva Cecilie
ABSTRACT: The study aims to describe anthropometric data of Greenlandic preschool children, blood pressure (BP) measures and effects of maternal smoking during pregnancy in a follow-up of the ACCEPT birth cohort. The study included 102 children (55 boys and 47 girls) aged 3.5–5.5 years. Anthropometric measures included weight, height, head circumference (HC), body mass index (BMI), waist and hip circumference, ratio for height/weight, waist/height, waist/hip and BP measurements. Overweight and obesity-prevalence was determined using the international obesity task force BMI references for children. Significant increases in anthropometrics from 3.5 to 5.5 years included weight, height, HC and hip circumference, whereas ratio for height/weight, waist/hip and waist/height decreased. Boys had significantly larger HC than girls. The prevalence of overweight and obesity was similar (35.1%) between genders. Mean systolic and diastolic BP were 104 and 68 mmHg, respectively. Children of mothers smoking during pregnancy had higher hip circumference, lower waist/hip ratio and higher diastolic BP. The study present updated anthropometric data and BP of Greenlandic preschool children and effects of maternal smoking during pregnancy. The prevalence of overweight and obesity was higher than previously reported and maternal smoking during pregnancy affected the child data. Abbreviations ACCEPT: Adaptation to Climate Change, Environmental Pollution and dietary Transition; BMI: Body Mass Index; BP: Blood Pressure; Circ: Circumference; DBP: Diastolic Blood Pressure; FFH: Fisher-Freeman-Halton exact test; HC: Head Circumference; H: Height; HDL: high-density lipoprotein; HiC: Hip Circumference; IOTF International Obesity Task Force, Max: maximum, Min: minimum, P25: 25th percentile, P75: 75th percentile, SBP: Systolic Blood Pressure, SD: Standard Deviation; VDLD: very-low-density lipoprotein; WaC: Waist Circumference, W: Weight, WHO: World Health Organization.